Impact of corona pandemic on paediatric surgical services: an institutional experience - Yadav, Ramdhani; Keshri, Rupesh; Chaubey, Digamber; Prasad, Ramjee; Kumar, Pranay; Bakhteyar, Asjad K.; Rahul, Sandip K. (International Surgery Journal, 2021)
Background: Corona-virus disease pandemic affected the health-care delivery at all institutions worldwide. Analysis of institutional data regarding management of surgical paediatric patients would reflect the impact and challenges which this pandemic brought by affecting the only functioning Paediatric surgery center in a poor province of a developing country. Objective was assessment of the impact of the COVID pandemic on the paediatric surgical services of a tertiary care center. Methods: Retrospective data of all patients operated at the only functioning tertiary center in Bihar with pediatric surgical services during the COVID-related lockdown period were collected and compared to the immediate pre-lockdown period and after the lockdown period. The impact of following the guidelines for surgery during this period was studied. Results: Both the number (0.8 cases/day) and types of patients operated in the lockdown period varied from the pre-lockdown period (3.62 cases/day). Elective cases were most significantly affected; neonatal, traumatic and malignancy cases could not be deferred and were therefore managed during the lockdown. Although the number of surgeries increased in unlock-down period (2.07 cases/day) and reached to a peak of 2.99 cases/day in the normal period between two phases of the pandemic; this increase was short-lived as the second phase of the pandemic again severely impacted the surgical care (1.38 cases/day). Conclusions: Corona pandemic severely impacted both the number and types of patients operated. Strict adherence to the protocol delayed emergency treatment and increased the cost of definitive management.